2007
DOI: 10.1128/jcm.01516-07
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Infections in Symptomatic and Asymptomatic Food Handlers in Japan

Abstract: Noroviruses are the leading cause of outbreaks of gastroenteritis in the world. At present, norovirus genogroup II, genotype 4 (GII/4), strains are the most prevalent in many countries. In this study we investigated 55 outbreaks and 35 sporadic cases of norovirus-associated gastroenteritis in food handlers in foodcatering settings between 10 November 2005 and 9 December 2006 in Japan. Stool specimens were collected from both symptomatic and asymptomatic individuals and were examined for norovirus by real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
145
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 183 publications
(161 citation statements)
references
References 31 publications
10
145
3
3
Order By: Relevance
“…Molecular epidemiological studies of NoV strains circulating in asymptomatic food handlers found that GII.4, which has higher transmissibility than other genotypes, was dominant (17)(18)(19). However, in our study, the NoV GII-12 strain was more prevalent than GII-4.…”
contrasting
confidence: 78%
“…Molecular epidemiological studies of NoV strains circulating in asymptomatic food handlers found that GII.4, which has higher transmissibility than other genotypes, was dominant (17)(18)(19). However, in our study, the NoV GII-12 strain was more prevalent than GII-4.…”
contrasting
confidence: 78%
“…Many norovirus outbreaks occurring in elder care facilities, summer camps, and hospitals were due to the food handler who were infected with the virus (13,(18)(19)(20)(21). In the Shenzhen elder care facility, the nurses, kitchen workers, and attendants cross-lived in the dormitory, and norovirus spread among the staff via daily contact in the dormitory; this affected the kitchen workers who had no direct contact with the elderly and induced foodborne transmission risks.…”
Section: Discussionmentioning
confidence: 99%
“…Ozawa et al, (2007) showed that many asymptomatic food handlers tested positive for NoV GII.4 strain in Japan. The number of virus shed by symptomatic and asymptomatic food handlers was similar, indicating the potential hazard of these highly contagious viruses.…”
Section: Occurrence In Food Handling Environmentsmentioning
confidence: 99%